Cultural Analysis of Shame as a Reflection of Malay Women at PGMI 2 Study Program Student of UIN Raden Fatah Palembang - Windy Anisa Dewi; Masayu Mutiah; Ayu Feryatma; Maryamah Maryamah (Innovative: Journal Of Social Science Research, 2023)
This research is to describe shame culture as a reflection of Melayu women to the students of PGMI 2 UIN Raden Fatah Palembang. The method used in this research is descriptive qualitative. The data collection techniques used were observation and document analysis. The results of this research are the importance of a culture of shame for a Melayu woman in the current era, examples of a culture of shame in Melayu women, how to implement a culture of shame, and the impacts that arise if a Malay woman does not have a culture of shame. The way to implement a culture of shame is by instilling that shame is not to limit oneself, instilling the importance of having a sense of shame, knowing the impact on oneself and the environment when ignoring shame in certain conditions, always carrying out positive activities, filtering every new culture, and realizing that every action performed is known to Allah SWT the All-Seeing.